Integration of Attendance Monitoring System Using RFID Technology with Web-based Facility Booking System for University Cleanroom Laboratory Application - Chiew, Pei Yi; Zainal, Nurfarina (Evolution in Electrical and Electronic Engineering, 2021)
This project introduced an integration of the attendance system and facility booking system for university cleanroom application that could vastly reduce human effort as compared to the traditional paper-based booking and attendance systems. The PHP programming languages integrated with the MySQL database were used for developing the booking system while the Radio Frequency Identification (RFID) technology was selected for the attendance system as it is cheaper in price as compared to other technologies. The web-based booking system has been successfully developed as it consisted of dual functions which were for the users and the administrator for booking and managing. This website has been integrated with the RFID technology attendance system. The attendance system was used to control and record the user, which only allows the user who was granted to enter the laboratory according to the booking request, as well as to record the entering and leaving time. This integration of the system can help the laboratory assistant to manage the laboratory efficiently and hence maintain a clean environment in the university cleanroom laboratory.